Towards semantic interoperability of protein data sources - Sidhu, Amandeep; Dillon, Tharam S.; Chang, Elizabeth (Springer-Verlag, 2006)
Several approaches for data interoperation identified by Karp have been implemented for biological databases. We extend Karp's approach for interoperation not only to protein databases but also to knowledge bases and other information sources. This paper outlines algebra for protein data source composition based on our existing work of Protein Ontology (PO). In this paper we consider the case of establishing correspondence between various protein data sources using semantic relationships over the conceptual framework of PO. Here we provide specific set of relationships over PO framework to cover data semantics for integrating data information from diverse protein data sources. These relationships help in defining semantic query algebra for PO to efficiently reason and query the instance store.